A Conceptual Framework for the Characterization of Petri Net Description Techniques - Madsen, Kim Halskov (DAIMI Report Series, 1984)
In this paper we present a conceptual framework for the characterization of Petri net description techniques, and we apply this framework to characterize some well-known techniques. The important point however, is that we feel that a conceptual framework (though perhaps not the one presented here) is essential for identifying and propagating description techniques. And surely for making progress in applications of nets, it is essential that we develop and communicate net description techniques that can deal with large systems.